2020
DOI: 10.1088/1755-1315/445/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the different procedures for preserving fish in Rivers State, Nigeria

Abstract: A survey was carried out in all the twenty three (23) Local Government Areas of Rivers State to evaluate the different methods of fish preservation in the State. The required information was collected by the use of questionnaires and direct interviews with the fish farmers and traders. The study holds that gender difference influenced approach to fish business, and that respondents are faced with problems which include lack of record keeping and finance. Others are inability of the State Government to introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In a study conducted in the coastal areas of Ondo state, Nigeria, it was observed that females dominated the processing sector (70%) [9]. According to Alonge et al [6], females are more likely to suffer health implications as they are more involved in fish preservation than males. The predominant age group was 31-40years (34.3%) followed by 16-30years (26.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in the coastal areas of Ondo state, Nigeria, it was observed that females dominated the processing sector (70%) [9]. According to Alonge et al [6], females are more likely to suffer health implications as they are more involved in fish preservation than males. The predominant age group was 31-40years (34.3%) followed by 16-30years (26.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been developed to meet this need; drying (dehydration), smoking, frying, salting, heating, roasting etc., most of which are practised in developing countries such as Nigeria. The principle behind these preservation methods is the elimination of microorganisms which cause spoilage and to halt biochemical reactions which will facilitate the spoilage, by reducing the water content of the food since moisture is necessary for the survival of microbes in the fish [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation